Education System in Bukhara Emirate - Gulamov Husanboy (International Journal on Integrated Education, 2022)
Ashtarkhanid rule, Mangit dynasty, transformation of Bukhara khanate into emirate, khanate and emirate educational systems, changes of power, influence of political situations on education, struggles for power.